The Effectiveness of Early Mobilization on Length of Stay (LOS) Postoperative Appendicitis Patients at The Benyamin Guluh Kolaka Hospital - Anita Anita; Narmawan Narmawan; Narmi Narmi (KLASICS, 2023)
Mobilization is an action to run as soon as possible and it is an important aspect of physiological function. Length of stay is an indicator in assessing the quality and efficiency of hospitals, but in Indonesia the average is still not ideal. The purpose of this study was to determine the effectiveness of early mobilization on Length Of Stay (LOS) in postoperative appendicitis patients. The quantitative study used was a quasy experiment using the control time series design method which was carried out involving a sample of 34 people consisting of 17 cases and 17 controls. Withdrawal of samples using purposive sampling technique. Data analysis used the Mann Whitney test. The results showed that the average length of stay of postoperative appendicitis patients was 5 days, which were given effective early mobilization which had a long length of stay as many as 5 people (29.4%), while those who were fast were as many as 12 other people (70 .6%), postoperative appendicitis patients who were not given ineffective early mobilization so that they had a long length of stay were 12 people (70.6%) while those who were fast were 5 people (29.6%). The conclusion of early mobilization is effective in Length Of Stay (LOS) in postoperative patients appendicitis from Ï value 0.036 (<0.05). It is recommended to increase knowledge of patients regarding the implementation of early mobilization.